Assessment of age and sex variability on haematological parameters of indigenous Punganur cattle - P, AVINASH; K, ASWANI KUMAR; B, PUNYA KUMARI (The Indian Journal of Animal Sciences, 2026)
This study aimed to assess the variability of sex and age on the hematological parameters of Punganur cattle. Blood samples were collected from 175 healthy Punganur cattle from Livestock Research Station (LRS), Sri Venkateswara Veterinary University and from farmers in the surrounding areas of Palamaner, Chittoor district, Andhra Pradesh across various age groups (Cows, Bulls, Heifers, Young bulls, Female calves, and Male calves) were collected and analysed. The results were categorized based on sex and age variations. Lymphocyte percentage (P<0.01) and granulocyte percentage (P<0.05) exhibited statistically significant variations, however, all other parameters did not show any differences under sex. Age-based analysis revealed significant differences (P<0.01) in Total Leucocyte Count Lymphocyte Count, Lymphocyte Percentage %, Granulocyte %, Total Erythrocyte Count, Haemoglobin, Mean Corpuscular Haemoglobin Concentration, Red Cell Distribution Width, Platelet Count, Platelet Distribution Width, and Plateletcrit, with Mean Corpuscular Volume showing significance at P<0.05. The findings could be used as reference values to differentiate normal physiological, nutritional and disease conditions for females, males and different age groups of Punganur cattle. This provides valuable insights for veterinarians and farmers, contributing significantly to the conservation of this endangered breed.